The utility of HRCT in the initial diagnosis of COVID-19 pneumonia—An Indian perspective - Kashyape, Rohan; Jain, Richa (Indian Journal of Radiology and Imaging, 2021)
A total of 1,499 patients who underwent High Resolution Computed tomography (HRCT) chest in the duration of 2 months for suspected COVID-19 pneumonia were included. Subjects included were those who had tested positive for the virus on RT-PCR, those with symptoms suspicious for COVID-19 infection awaiting results for the RT-PCR test or with negative result but strong clinical suspicion as well as those with exposure to proven patients based on contact tracing. Thus, both symptomatic as well as asymptomatic patients were included. The positive predictive value of HRCT was 85%, sensitivity was 73% for all patients. Overall, accuracy was 68%. There was no significant difference in these values for symptomatic and asymptomatic individuals. These results were also independent of the time of scan from the onset of symptoms or contact. Thus, we propose that HRCT is an excellent adjunct for initial diagnosis of COVID-19 pneumonia in both symptomatic and asymptomatic individuals in addition to the role of prognostic indicator for COVID-19 pneumonia.
Keywords: COVID-19; diagnosis; high resolution computed tomography